Linking MDA Levels and Blood Glucose in Streptozotocin-Induced Rat Diabetes: Implications for Diabetic Complications and Therapeutic Strategies - Evelyn Angie; Ermi Girsang; Refi Ikhtiari (Jurnal Penelitian Pendidikan IPA, 2024)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels resulting from insulin deficiency or resistance. Streptozotocin, a potent diabetogenic agent, is commonly employed to induce experimental diabetes by selectively damaging pancreatic beta cells, resulting in insulin deficiency and hyperglycemia. Elevated Malondialdehyde (MDA) levels, indicative of oxidative stress and lipid peroxidation, are closely linked to diabetic complications. This study aimed to investigate the association between MDA levels and blood glucose in Streptozotocin-induced rat diabetes, shedding light on potential therapeutic strategies. Spectrophotometric analysis was utilized to quantify MDA levels in rat tissues, providing insights into the extent of oxidative damage. The results revealed a significant correlation between MDA levels and blood glucose, highlighting the role of oxidative stress in diabetic pathogenesis. These findings underscore the importance of targeting oxidative stress in diabetes management to prevent complications. In conclusion, the study emphasizes the relevance of monitoring MDA levels as a biomarker for assessing oxidative stress in diabetic conditions and guiding therapeutic interventions.